0655 The Impact of Slow-Wave Sleep Disruption on Response Inhibition in Individuals with Depression. (25th May 2022) - Goldstein, Elena; Palermo, Emma; Costello, Samantha; Games, Margaux; Goldschmied, Jennifer
Abstract: Introduction: Individuals with Major Depressive Disorder (MDD) exhibit reductions in slow-wave sleep (SWS) and impairments in neuroplasticity. For example, decreased executive functioning, including poorer response inhibition compared to healthy controls, has been reported. SWS has been implicated in the homeostatic regulation of neuroplasticity, however it is unclear if the cognitive deficits seen in MDD are directly associated with SWS. In this study, we aimed to examine if disrupting SWS, thereby altering neuroplasticity, could improve response inhibition in patients with MDD. Methods: Participants in this study (n=29) included 19 individuals with depression and 10 healthy controls. Data were collected after two overnight sleep studies separated by one week. During one of the two nights, participants' slow-wave sleep was disrupted via auditory tones. In the morning following each night, participants completed a neurocognitive task battery including an auditory Go/No-Go task. Accuracy scores were calculated as the percentage of trials on which the participant responded correctly to the "Go" or "No-Go" stimulus. Repeated measures ANOVA and paired t-tests were then performed to examine changes from baseline to SWD, assessing the role of SWD on response inhibition. Results: Following SWD, depressed participants' performance on the Go/No-Go task was significantly more accurate (t=-2.067, p=.027) than following baseline sleep, while healthy controls showed no significant change between nights (t=-.231, p=.411). The interaction between group (MDD vs. healthy control) and condition (baseline vs. SWD) did not reach statistical significance (p=.175). Conclusion: In a sample of individuals with depression, accuracy on the Go/No-Go task improved significantly after undergoing SWD compared to following baseline sleep, indicating improved response inhibition. However, healthy controls did not exhibit this same improvement in accuracy. These findings highlight a possible disparity in the role that SWS plays in the regulation of neuroplasticity in those with depression and those without. Support (If Any): Goldschmied: K23MH118580 (NIMH)